Applications of mainstream economic theories to the construction industry : transaction costs - Abdul Rashid, Abdul Aziz; Afzan, Ahmad Zaini (Edward Elgar Publishing Ltd., 2022)
The origins of transaction cost as an economic concept can be traced to Ronald Coase’s (1937) paper entitled ‘The nature of the firm’ (and his subsequent work, ‘The problem of social cost’ which came out in 1960) in which he posed the question, ‘Why does a firm emerge at all in a specialised exchanged economy’ (Coase, 1937, p. 40)? In trying to answer this puzzle, he raised doubts about the prevailing assumption among economists at the time that there are no cost implications accompanying exchange relationships in markets, a conundrum which Oliver E. Williamson took it upon himself to resolve. Williamson’s radical approach was to depart from the then-prevailing economic orthodoxy by integrating economics, law and organisation theory; although economics was first among equals (Williamson, 1998). Its gestation period stretched from the 1920s to the 1970s (Williamson, 2008). At the same time, he infused into the transaction construct his own original ideas regarding vertical integration and the theory of the firm (Mahoney, 2005). Following Commons (1924, 1934), he reinterpreted the basic unit of analysis as the transaction (Williamson, 1985). Reducing transaction cost then becomes the engine of analysis (Williamson, 2008).